GPS-psevdokinematic survey method - Kuhar, Miran (Geodetski vestnik, 1993)
The article describes the measurement and calculation of point's coordinates for photogrammetric survey method. Further, the pseudokinematic observation method and a 12 points measurement example on the Pivka territory is described. Calculated are coordinates of points in the GK system and the accuracy analysis.
Keywords: accuracy; control points; fotogrametrija; Global Positioning System; GPS; GPS pseudokinematic survey method; natančnost; oslonilne točke; photogrammetry; psevdokinematična metoda; Slovenia; Slovenija